Light-Driven Alignment - Antonyuk, Boris P. (Springer Series in Optical Sciences, 2009)
This book deals with influencing the properties of solids by light-driven electron transport. The theoretical basis of these effects, light-driven ordering and self-organisation, as well as optical motors are presented. With light as a tool, new ways to produce materials are opened.